A case-based medical curriculum for the 21st century: The use of innovative approaches in designing and developing a case on mental health. (4th May 2017) - Hassoulas, Athanasios; Forty, Elizabeth; Hoskins, Mathew; Walters, James; Riley, Stephen
Abstract: The introduction of case-based learning (CBL) by the School of Medicine at Cardiff University has encouraged innovation in medical teaching and learning. During years one and two of the modernized MBBCh program, students complete 17 cases as part of the newly developed C21 curriculum that emphasizes a patient-oriented and student-centered approach to learning. The mental health case, which is presented in year 2, incorporates a number of novel teaching resources that aim to enhance the students' learning experience and to further reinforce the patient-oriented and community-based philosophy of C21. These include the use of fictionalized video diaries, virtual patient cases, e-learning workbooks, an interactive practical session, and community placements. Novel teaching methods and resources were evaluated by students in terms of effectiveness and value as learning resources through the administration of a structured mixed questionnaire. The results revealed that students valued the inclusion of these resources, which they evaluated as having contributed to their understanding of the subject area. Furthermore, the case was found to have had an impact on student interest in psychiatry as a specialty as well as a career choice. The positive student evaluation of this case supports the innovations in teaching delivery inspired by C21.